MODEL REHABILITASI SOSIOPSIKOLOGIS DAN PENINGKATAN KETAHANAN PANGAN RUMAH TANGGA TERDAMPAK KERAWANAN DI KAWASAN PENGUASAAN TERORIS GUNUNG BIRU, POSO, SULAWESI TENGAH - Ali, Muhammad Nur; Mahfudz; Ramlan; Rahman, Nurdin (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Tadulako, 2018)
Mt. Biru is a fertile wilderness area in Tamanjeka Hamlet, Masani Village, Poso Pesisir District, Poso Regency. At 2006, the Mt. Biru area was widely known as the movement basis of the East Indonesia Mujahidin group led by Santoso. As an area inhabited and/or controlled by terrorists, the peace of the population becomes disturbed, even frightened, because there are counter-indications between terrorists and security personnel from the military/police. The article from this research discusses sociopsychological rehabilitation and increases the food security of households affected by vulnerability in the Mt. Biru area. The social conditions of the community in the process and social interaction both within their internal and external circles experience rigidity and are very limited, confined, and even fearful. Sociologically, the process and social interaction, due to persistent fear, are gradually becoming psychological symptoms that influence other aspects of life, especially in the economic field as farmers. Significant decline in farmer's productivity due to the loss of sociopsychological strength due to terror and incidents, decreasing family food security, and other generative impacts in time will emerge.